2014
DOI: 10.1016/j.toxrep.2014.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the impact of genetically modified LibertyLink ® maize on reproductive function and progeny development of Wistar rats in three generations

Abstract: This publication presents the assessment of the impact of genetically modified (GM) LibertyLink® maize on reproductive function, prenatal and postnatal progeny development of Wistar rats over three generations. The animals were divided into two groups, which were fed with rodent diet with inclusion of GM LibertyLink® (‘test’ group) and non-GM near-isogenic counterpart (‘control’ group) maize varieties. The maize was included into the diet at maximum possible level (between 32 and 33%) not causing nutritional i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…The study was conducted on pregnant and lactating Wistar rats at the clinic of laboratory animals of the Federal State Budgetary Institution “Institute of Nutrition” of the Russian Academy of Medical Sciences. During the preconception period and throughout the pregnancy and lactation, the females received the standard semi-synthetic diet according to [ 21 ]. The gestation period of the females was 20 days following conception; lactation period – on average 10–11 days after the birth of offspring.…”
Section: Methodsmentioning
confidence: 99%
“…The study was conducted on pregnant and lactating Wistar rats at the clinic of laboratory animals of the Federal State Budgetary Institution “Institute of Nutrition” of the Russian Academy of Medical Sciences. During the preconception period and throughout the pregnancy and lactation, the females received the standard semi-synthetic diet according to [ 21 ]. The gestation period of the females was 20 days following conception; lactation period – on average 10–11 days after the birth of offspring.…”
Section: Methodsmentioning
confidence: 99%
“…GM rice, soybean, maize, and wheat, alone or in combination, have been fed to rats, broiler chickens, layer hens, dairy cows, monkeys, frogs, and pigs. Most of the studies conducted lasted for up to 90 days and recorded pathological, hematological, histopathological, serum chemistry, macroscopic, food intake, and reproduction-related characteristics (Tyshko et al 2014, Tyshko andSadykova, 2016). In all the studies, only minor or no adverse changes were recorded and the general conclusions were that GM food and feed have no hazardous effects compared with non-GM diets.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…ree studies reported sperm parameters over 90 days, while others indicated shorter periods [5][6][7]. One study was conducted on mice [8] and rats [5][6][7][9][10][11]. GM crops were rice in 4 studies [6][7][8][9] and maize [5] and potato [11] in the other studies.…”
Section: Resultsmentioning
confidence: 99%